ЗНАЧИМОСТЬ ОБРАЗОВАНИЯ И ОБУЧЕНИЯ ВО ВЗГЛЯДАХ АЛЬ-ФАРАБИ (Journal of Philosophy Culture and Political Science, 2022)
Education with its general meaning is considered as the process of acquiring desired behaviours and knowledge. Education is understood as the process of transferring all the information needed in the life journey the individual who has the ability to comprehend as well as the process of teaching the behavior patterns that the society expects from the individual. In this context education has a dual structure. One side of this is formed by the individual and the other side is formed by society. Thus, the education processappeors as a process that provides both individual and social benefit. Educating the individual in a desired way includes providing the desired information in a desired way includes providing the desired information to the individual as well as acquisitioning a set of desired values. İn this context sensitivity to certain values that the society expert from the individual can be gained thanks to education. The acquisition of values to the individual is a philosophical problem area in itself. Farabi as important phisopher his views about education provide us with enlightening information about the nature and purpose of education. In this article as a social phenomenon problem of education and pedagogics in philosophical system of Al-Farabi are versatily considered. This phenomenon is closely connected with soul of the person and also confirms that each person since early years is going to become the member of society, to reach the level of perfection, and as a result to achieve the set goal. According to Al-Farabi, all activity directed on education is an of the person of values, knowledge and practical opportunities in society, in some period of time. If a main goal of education is achievement of perfection by the personality, the human life purpose in the world - to achieve the highest level of happiness - absolute good.Al-Farabi unites all levels of knowledge and practice in the purpose of receiving knowledge: any received theoretical knowledge has to be put into practice.Key words: Education, theory, practice, political leader, moral, personality, pedagogy, intellectual knowledge, didactics.